Difficulty in Assessing Quality of Life Outcomes in a Fluctuating Disease: A Hypothesis Based on Gastroparesis - Vic Velanovich (Gastroenterology Research and Practice)
An underlying assumption of quality of life outcome research is that after some intervention a “steady-state” of quality of life is reached which can be identified as an endpoint, and, hence, the “outcome.” However, in some disease processes, no so such steady-state is reached. The hypothesis presented is that a disease process with a waxing and waning course will make it difficult to determine a quality of life endpoint. After clinical observation, a pilot study of patients with either diabetic or idiopathic gastroparesis with gastric neurostimulation their records were reviewed to identify the number of clinic visits, the number of clinic visits in which the patients were asymptomatic, much improved, improved, no change, worse, or much worse. These changes were defined as “transitions.” A “transition ratio” was calculated by dividing the number of transitions by the number of clinic visits. Preliminary results showed that of 32 patients, the median number of clinic encounters was 8 (1–35), and the median number of transitions 4 (0–22). The average transition ration was 0.56±0.31. In the case of gastroparesis, over half of all clinical encounters were associated with a transition. The implication of the hypothesis and preliminary finding suggests a difficulty to identify when the symptomatic endpoint was reached. Other methods to assess the effects of treatment in such a disease process are required to fully understand the effects of treatment on quality of life.